Analisis Tingkat Komponen Dalam Negeri (TKDN) Pada Proyek Konstruksi UPT BKN (Unit Pelaksana Teknis Badan Kepegawaian Negara) Gorontalo - Muhammad Gandhy Maudara; Moh Yusuf Tuloli; Arfan Utiarahman (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The Domestic Component Level (TKDN) policy plays a crucial role in enhancing national industrial competitiveness, reducing import dependency, and stimulating economic growth in Indonesia. This study analyzes the TKDN implementation in the construction project of the Technical Implementation Unit of the State Civil Service Agency (UPT BKN) Gorontalo to evaluate the contribution of local materials, labor, and equipment to project costs. This research adopts a quantitative descriptive approach by collecting secondary data from project documents, including material specifications, unit price analyses (AHSP), and budget plans. The TKDN calculation follows Regulation of the Ministry of Industry No. 16/M-IND/PER/2/2011, focusing on three key components: materials, labor, and equipment. The findings indicate that the project achieved a TKDN value of 55.57%, exceeding the government’s minimum requirement of 25%. Local materials such as mortar, sand, and lightweight bricks, along with the full engagement of Indonesian workers (100% TKDN), significantly contributed to this outcome. However, imported heavy equipment and mechanical components remain a challenge. The study highlights that optimizing domestic products and workforce utilization in construction projects effectively strengthens national industrial independence. Recommendations include simplifying TKDN certification, increasing local production capacity, and fostering technology transfer through international collaboration.